Long‐term survival and cognitive function according to blood pressure management during cardiac surgery. A follow‐up. Issue 7 (27th April 2020) - Larsen, Mo H.; Draegert, Christina; Vedel, Anne G.; Holmgaard, Frederik; Siersma, Volkert; Nilsson, Jens C.; Rasmussen, Lars S.
Abstract : Background: Cardiac surgery is associated with a risk of complications, including post‐operative cognitive dysfunction (POCD). In the randomized Perfusion Pressure Cerebral Infarcts (PPCI) trial, we allocated cardiac surgery patients to either a low‐target mean arterial pressure (40‐50 mm Hg) or a high‐target pressure (70‐80 mm Hg). The study found no difference in the volume of new ischemic cerebral lesions nor POCD, but 30‐day mortality tended to be higher in the high‐target group. In the present study we did a long‐term 3‐year follow‐up to assess survival and level of cognitive functioning. The primary hypothesis was that patients allocated to a high‐target blood pressure had a higher long‐term mortality at 3‐year follow‐up. Methods: We determined long‐term mortality of patients included in the PPCI trial at 3‐year follow‐up using national registries and we assessed POCD using a cognitive test battery. Subjective level of functioning was assessed with questionnaires. POCD and subjective functioning at follow‐up were evaluated in logistic regression models. Results: Among the 197 patients who participated in the original study, there was no significant difference in mortality over a median of 3.4 years according to blood pressure target during cardiopulmonary bypass (hazards ratio 1.23 [high vs low] 95% confidence interval: 0.50‐3.02, P  = .65). POCD was found in 18.9% and 14.0% in the high‐target and low‐target groups, respectively adjusted odds ratio 1.01 (CI 95% 0.33‐3.12). No differences were found for subjective functioning between groups. Conclusions: No difference in mortality nor in the level of cognitive functioning was found according to blood pressure target during cardiac surgery long‐term at 3‐year follow‐up.